Phenomenological Study of Dependence on Artificial Intelligence and Self-Coping of Academic Problems - Fadhila Rahmawati; Dindin Solahudin; Hajir Tajiri (Scidacplus, 2026)
This study explored of emotional dependence on Artificial Intelligence (AI) and the self-coping strategies they use to address academic challenges from an Islamic Counseling perspective. This study employed a qualitative approach with the Colaizzi descriptive phenomenology method. The subjects were 20 with specific criteria Student status, intensity of AI usage, specific experience, and voluntary participation active students at Sunan Gunung Djati State Islamic University, Bandung, selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation using a semi-structured interview guide. The Genesis and Evolution of AI Interaction, Psychological and Relational Dynamics of Dependence and The Hierarchy of Coping Mechanisms The results revealed two main findings. First, the function of AI shifted from being merely an academic aid to a source of emotional support as students experienced increasing academic pressure. Second, AI tended to be used as a dominant self-coping strategy, thus reducing the use of spiritual coping in dealing with academic pressure. All informants continued to view Allah as the primary source of peace. This spiritual awareness strengthened when students realized the limitations of AI in meeting their emotional needs fully. The findings of this study demonstrate the importance of developing Islamic Guidance and Counseling services that are responsive to technological developments and the psychological dynamics of students in the academic environment.